AUTOIMMUNE/INFLAMMATORY SYNDROME INDUCED BY ADJUVANTS (ASIA): AUTOIMMUNE/INFLAMMATORY SYNDROME INDUCED BY ADJUVANTS (ASIA) - Mathews, Gerard Jason; Subramanian, Seetha Devi; Yee, Teh When; Mathews, Joel; Merican, Nor Shaffinaz Yusoff Azmi; Ismail, Shartiyah (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Autoimmune/inflammatory syndrome induced by adjuvants (ASIA), also known as Shoenfeld’s syndrome, encompasses a spectrum of autoimmune conditions and responses triggered by exposure to substances with adjuvant activity such as vaccines. CASE A healthy 43-year-old male with no known medical illness or family history of thyroid disorder developed painful thyroiditis after receiving his influenza vaccination. He undergoes regular health checkups, which have consistently shown normal results, including previous thyroid function tests (TFT). Patient received his influenza vaccine (Vaxigrip tetra) and developed left sided neck pain and severe thyrotoxicosis symptoms after 1 week. Blood investigation done showed free T4 25 pmol/L, TSH <0.01 m IU/L and a raised CRP. Physical examination revealed a tender diffuse goitre and fine tremors. Ultrasonography of the neck was done with the impression of subacute thyroiditis. These findings fulfilled the Japanese Thyroid Association (JTA) criteria for subacute thyroiditis. A Tc-99m Pertechnetate also confirmed the findings of thyroiditis. The patient was commenced on oral prednisolone 25 mg daily (0.5 kg/BW/ day) with a tapering regimen over 2 weeks. He also received oral celecoxib 200 mg daily for 5 days and oral propranolol 20 mg daily. He gradually improved upon the 2-week clinic review and all medications were discontinued. Upon reevaluation at 3 months, thyroid function tests normalized, and the thyroid ultrasound displayed the resolution of thyroiditis characteristics, accompanied by amelioration of all symptoms. CONCLUSION Subacute thyroiditis is an inflammatory thyroid condition characterized distinctly by painful enlargement of the thyroid. Transient hyperthyroidism is a hallmark of subacute thyroiditis where the inflamed thyroid gland releases unregulated excessive thyroid hormone into the bloodstream, leading to thyrotoxicosis symptoms. In this case, we treated our patient with a short-term 2-week combination of steroids + NSAIDs which showed noninferior efficacy to the traditional long-term steroids (4-8 weeks).